2017
DOI: 10.1371/journal.pone.0188075
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of cell-surface B-cell receptor-associated protein 31 contributes to poor survival of non-small cell lung carcinoma cells

Abstract: B-cell receptor-associated protein 31 (BAP31) is an endoplasmic reticulum (ER) membrane protein which plays a role as a molecular chaperone for the newly synthesized transmembrane proteins. BAP31 is also an important apoptosis regulator for extrinsic apoptosis induction in the ER membrane. Recent studies have shown that BAP31 is also expressed on the surface of embryonic stem cells. However, the function of cell surface BAP31 (csBAP31) still remains unclarified. In an attempt to search for surface markers on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…As a cancer/testis antigen, BAP31 has been correlated with patient survival in multiple kinds of cancer (Dang et al, 2018;Xu et al, 2019). BAP31 was up-regulated in cervical cancer, malignant melanomas and lung carcinomas and its high expression indicated a poor prognosis (Yu et al, 2015;Seo et al, 2017;Dang et al, 2018). In the present study, we have elucidated that BAP31 was up-regulated in HCC compared to normal tissues and high BAP31 expression contributed to poor prognosis, which suggested BAP31 might serve as a potential prognostic factor in HCC.…”
Section: Discussionsupporting
confidence: 50%
“…As a cancer/testis antigen, BAP31 has been correlated with patient survival in multiple kinds of cancer (Dang et al, 2018;Xu et al, 2019). BAP31 was up-regulated in cervical cancer, malignant melanomas and lung carcinomas and its high expression indicated a poor prognosis (Yu et al, 2015;Seo et al, 2017;Dang et al, 2018). In the present study, we have elucidated that BAP31 was up-regulated in HCC compared to normal tissues and high BAP31 expression contributed to poor prognosis, which suggested BAP31 might serve as a potential prognostic factor in HCC.…”
Section: Discussionsupporting
confidence: 50%
“…The cleaved BCAP31 fragment, p20, is a potent inducer of apoptosis when expressed ectopically 36 . Therefore, the enhanced expression of BCAP31 could contribute to the poor survival of NSCLC cells 37 , which should benefit patients. However, full-length BCAP31 inhibits caspase activity 38 , and in cancer, apoptosis-resistance mechanisms are used to evade cell death 39 .…”
Section: Discussionmentioning
confidence: 99%
“…B-cell receptor-associated protein 31 (BAP31), an important apoptosis regulator for extrinsic apoptosis induction in the ER membrane, plays ar ole as am olecular chaperone for the newly synthesized transmembrane proteins. [18] LPCAT3 plays am ajor role in phospholipidm etabolism in the liver and intestine. [19] It was reported that TM9SF3 participates in tumor invasion and serves as ap rognostic factor,a nd might be ap otential diagnostic and therapeutic targetf or scirrhoustype gastric cancer.…”
mentioning
confidence: 99%